Dramat ojcowskiej miłości (Łk 15,11-32) - Muszytowska, Dorota (Verbum Vitae, 2013)
The parable of the father and his two sons in the Gospel of Luke (Luke 15:11-32) makes part of a series of parables depicting the attitude of God toward sinful man. It is the attitude of seeking, concern, love, and joy in the presence of which nobody, even the greatest sinner, is excluded. The present article focuses on that attitude by exposing relationships between father and his two sons. Despite the fact that the narrative presents the events from the perspective of the sons, the father can be considered the main character of the parable. The story of the sons shows the drama of father’s love which was rejected and misunderstood by them. Both sons lose their dignity by denying their father’s love, but only the younger seems to realize it. The father shows both of them the same love and assures them that in his eyes they have never lost their sonship and they have never been deprived of it. Each of the children has to be re-adopted; each in his own way indicated by the father. The younger has to accept paternal forgiveness which is full of mercy and joy prompted by his return. The elder, on the other hand, has to imitate the mercy and joy offered by the father to his younger son.